Survey the effect of acupressure on sixth spleen pointon primary dysmenorrheal relief - Zohreh Sadat; Mahboobeh Kafaei Atrian; Maliheh Sarvieh; Nahid Sarafraz; Fatemeh Abbaszade; Mohammad Jafarabadi; Tahereh Dehdari (Journal of Holistic Nursing and Midwifery)
Abstract